Leading Through Placemaking and Boundary Spanning: Rural Christian Higher Education for the Common Good. Issue 1 (15th March 2018) - Mobley, Jennifer Scott; Rine, P. Jesse; Kemeny, P. C.; Messer, H. Collin
ABSTRACT: Evangelical colleges and universities situated in rural communities are uniquely positioned to bridge the ever-widening cultural, economic, and political divide that threatens American democracy. However, success in this endeavor will require an appreciation for what it means to be a neighbor in this particular context. Thus, this article begins with a brief overview of how the common good has been conceptualized and pursued throughout the history of American higher education, followed by a description of features common to rural contexts. Next, a group of 31 member institutions of the Council for Christian Colleges and Universities is identified as rurally located, and their group characteristics are contrasted with their urban counterparts. Attention then turns to the contours of community engagement in the rural context, and the potential for rural evangelical colleges and universities to fulfill the place-based roles of stewarding and anchoring is explored. The article concludes by casting a vision for the common good in which Christian institutions of higher education partner with their surrounding communities to co-create a shared perspective, shared knowledge, and shared places.